Characteristics of the Board of Directors and Company Performance New Zealand Evidence - Md. Borhan Uddin Bhuiyan; Jamal Roudaki; Murray B. Clark (Journal of Accounting, Business and Management (JABM), 2010)
This study examines the relationship between characteristics of the board of director and firm performance. Few research studies examine this issue, particularly with Return on Assets (ROA) as a performance indicator. Companies that were listed on the New Zealand stock exchange (NZX) over the period 2000 to 2007 were examined, and the results showed that selected characteristics of the board of directors are positively related to firm performance. Specifically, the characteristics studied were: the size of the board, the independence of directors, the tenure of directors, the outside involvement of board members, the frequency of board meetings, the length of time the Chief Executive Officer (CEO) has been in the company, and the extent of shareholding held by the directors.